2002
DOI: 10.1110/ps.16502
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ligand‐receptor alliances by “SEA” module‐mediated cleavage of membrane‐associated mucin proteins

Abstract: A mechanism is described whereby one and the same gene can encode both a receptor protein as well as its specific ligand. Generation of this receptor-ligand partnership is effected by proteolytic cleavage within a specific module located in a membrane resident protein. It is postulated here that the "SEA" module, found in a number of heavily O-linked glycosylated membrane-associated proteins, serves as a site for proteolytic cleavage. The subunits generated by proteolytic cleavage of the SEA module reassociate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…This processing has been implicated in cell-to-cell communication, apoptosis, signaling, sensing of chemical or mechanical stress, defense against infections and chemical damage, and cancer (37,43,44). Many of the above mentioned proteolytic events occur at SEA modules (37,42), and it was hypothesized that all membrane-residing proteins containing a SEA module will undergo cleavage as part of a regulatory mechanism based in receptor alliances (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This processing has been implicated in cell-to-cell communication, apoptosis, signaling, sensing of chemical or mechanical stress, defense against infections and chemical damage, and cancer (37,43,44). Many of the above mentioned proteolytic events occur at SEA modules (37,42), and it was hypothesized that all membrane-residing proteins containing a SEA module will undergo cleavage as part of a regulatory mechanism based in receptor alliances (45).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, shedding is due to specific membrane proteases (45). In other cases, autoproteolysis takes place.…”
Section: Discussionmentioning
confidence: 99%
“…The other TM mucin genes are dispersed through the genome. A number of structural characteristics are common to TM mucins: SEA domains that form cleavage sites have been identified in MUC1, MUC3A and MUC3B, MUC12, and MUC13 [15], whereas one or more epidermal growth factor-like domains are present in MUC3A, MUC3B, MUC4, MUC12, MUC13, and MUC17. Although the true role of TM mucins remains unclear, there is emerging evidence that they are involved in host defense from infection acting as both a physical barrier and by modulating epithelial growth and apoptosis via signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray structure of recombinant ME ICA512 (Fig. 1B) (18), encompassing amino acids 468 to 558, revealed that this region displays a ferredoxin-like fold related to the SEA (sea urchin sperm protein, enterokinase, agrin) domain, which is known to promote oligodimerization (24)(25)(26)(27)(28). Accordingly, both crystallized (18) and soluble (19) versions of ME ICA512 form dimers resulting from the antiparallel pairing of ␤2-␤2 or ␤4-␤4 strands ( Fig.…”
Section: Resultsmentioning
confidence: 99%